2010
DOI: 10.1294/jes.21.73
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Thoroughbred Racing Performance

Abstract: Using a dataset of 274 male Thoroughbred racehorses in the United States, we study the effect of age on racing performance. Beyer speed figures, which are uniform measures of racing performance across distance and racing surface, are utilized in this study. A system of equations is estimated to determine quadratic improvement and decline in racing performance. We find that a typical horse’s peak racing age is 4.45 years. The rate of improvement from age 2 to 4 1/2 is greater than the rate of decline after age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…However, the picture is not simple. In some investigations, as here, risk is carried disproportionally by young and by older horses, while middle‐aged animals tend to have relatively low risk . Young horses may more frequently have problems with temperament and tractability, be predisposed to injuries reflecting skeletal immaturity and be more prone to fatigue, while older horses may suffer from cumulative damage.…”
Section: Discussionmentioning
confidence: 82%
“…However, the picture is not simple. In some investigations, as here, risk is carried disproportionally by young and by older horses, while middle‐aged animals tend to have relatively low risk . Young horses may more frequently have problems with temperament and tractability, be predisposed to injuries reflecting skeletal immaturity and be more prone to fatigue, while older horses may suffer from cumulative damage.…”
Section: Discussionmentioning
confidence: 82%
“…Four-year-old Brazilian Thoroughbreds were significantly faster than horses of other ages for all race distances, except for 1100 m. However, the horses older than five years showed a significantly lower performance than the other ages for all race distances, excluding the 1100 m (Mota et al, 2005). Gramm and Marksteiner (2010) observed that peak age was 4.45 years and the lowest age was two for race performance in Thoroughbred in USA. On the other hand, race performance was not significantly affected by mother age.…”
Section: Discussionmentioning
confidence: 65%
“…When additional genomic information becomes available for the equine genome, such as a new genome assembly or newly identified genes, this information can be applied to our database. We used two breeds of horse, and each individual was sacrificed in their golden age as racing ability (Gramm and Marksteiner, 2010). The methylation patterns can change as developmental state, sex, and age dependent Martino et al, 2013), and this database could provide a reference methylation state for users in further studies.…”
Section: Resultsmentioning
confidence: 99%